2019
DOI: 10.31234/osf.io/7jwrz
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

14 challenges and their solutions for conducting social neuroscience and longitudinal EEG research with infants

Abstract: The use of electroencephalography (EEG) to study infant brain development is a growing trend. In addition to classical longitudinal designs that study the development of the neural, cognitive and behavioural function, new areas of EEG application are emerging, such as novel social neuroscience paradigms using dual infant-adult EEG recordings. However, most of the experimental designs, analysis methods, as well as EEG hardware were originally developed for single-person adult research. When applied to the study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(34 citation statements)
references
References 40 publications
0
32
0
Order By: Relevance
“…These components were then projected out (mean and standard deviation of number of rejected components: 1.15±1.13). In general, because the separation between noise and signal ICA components in infant EEG data is less distinct than in adults (Noreika et al, 2020), we rejected components conservatively. The data was re-referenced to a common average reference.…”
Section: Preprocessingmentioning
confidence: 99%
“…These components were then projected out (mean and standard deviation of number of rejected components: 1.15±1.13). In general, because the separation between noise and signal ICA components in infant EEG data is less distinct than in adults (Noreika et al, 2020), we rejected components conservatively. The data was re-referenced to a common average reference.…”
Section: Preprocessingmentioning
confidence: 99%
“…With the advance of neuroimaging techniques, the last decades saw an additional increase in studies relying on infant EEG ( Azhari et al, 2020 ). However, measuring EEG in infants is not a straightforward task, and comes with its own challenges, often resulting in high attrition rates ( Noreika et al, 2020 ; Stets et al, 2012 ). Fortunately, there is literature focusing on explaining and improving the methodology (cf.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, in the fast-advancing field of social neuroscience, dual-EEG (concurrent neural recording from two interacting individuals) is increasingly being used in naturalistic settings to track dynamic changes in interpersonal neural coupling, even between infants and adult caregivers [ 39 , 40 , 41 ]. Although there are unique technical challenges associated with the collection and interpretation of naturalistic dual-EEG data, particularly with infant participants [ 42 ], the mother–infant interpersonal neural network has been found to be exquisitely sensitive to changes in maternal emotional state [ 43 ] or parenting stress [ 44 ], and also predicts the likelihood of infant social learning from their parent [ 41 ]. Dual-EEG studies with adults have demonstrated that interpersonal neural coupling may also index empathy, differentiate the emotional tone of the conversation [ 45 ], and signify the degree of cooperation between interacting members of a dyad [ 46 , 47 ].…”
Section: Moving Beyond the Individual To A Multi-domain Neurophenomentioning
confidence: 99%